Star-shaped tetrathiafulvalene oligomers towards the construction of conducting supramolecular assembly - Iyoda, Masahiko; Hasegawa, Masashi (Beilstein Journal of Organic Chemistry, 2015)
The construction of redox-active supramolecular assemblies based on star-shaped and radially expanded tetrathiafulvalene (TTF) oligomers with divergent and extended conjugation is summarized. Star-shaped TTF oligomers easily self-aggregate with a nanophase separation to produce supramolecular structures, and their TTF units stack face-to-face to form columnar structures using the fastener effect. Based on redox-active self-organizing supramolecular structures, conducting nanoobjects are constructed by doping of TTF oligomers with oxidants after the formation of such nanostructures. Although radical cations derived from TTF oligomers strongly interact in solution to produce a mixed-valence dimer and π-dimer, it seems to be difficult to produce nanoobjects of radical cations different from those of neutral TTF oligomers. In some cases, however, radical cations form nanostructured fibers and rods by controlling the supramolecular assembly, oxidation states, and counter anions employed.
Keywords: conducting fibers; star-shaped molecules; supramolecular assembly; tetrathiafulvalene oligomers